LITERATURE REVIEW: PSYCHOLOGICAL FACTORS AFFECTING ONLINE SHOPPING BEHAVIOR DURING THE COVID-19 PANDEMIC - Olivia Safira Maharani; Nabila Jilan Ulayya; Wahyu Rahardjo (Universitas Gunadarma, 2022)
The COVID-19 pandemic can be defined as more than just a health crisis as it has a strong impact on society and the economy. The COVID-19 outbreak has dramatically changed shopping behavior, which was originally visiting and buying offline, now became online. Several studies indicate that new habits formed now will endure beyond this crisis, permanently changing what we value, how and where we shop; The purpose of this study is to identify psychological factors that may promote and influence online shopping behavior during the COVID 19 pandemic. The method used is a literature review where the author collects 23 journals from the digital library and Google Scholar and then concludes the results of the related topics. The results showed that there are five psychological factors, including (1) positive perceptions of the use of web online shopping; (2) online shopping self-efficacy; (3) negative emotion factors and fear of COVID-19; (4) motivation to adapt; and (5) social influence. This research can be useful for sellers or producers to get good business by paying attention to the psychological side of consumers in online buying and selling transactions during the pandemic.